Four Middle English Notes: Calf ’shank’, Silk ’prey’, Clanvowe’s cuckoo and William Worcestre’s ’Doynton’ - Andrew Breeze, Andrew Breeze (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen